فعالية تعليم المناظرة العلمية لترقية مهارة الكلام : The Effectiveness of Teaching Scientific Debate to Enhance Speaking Skills - Rahayu, Ayu; Abicandra, Muhammad Nidhom Hamami (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2023)
Debate is one of the linguistic skills from the branch of speech skill that enjoys the highest level, after several arts such as dialogue / speaking, rhetoric, presenting the story, and reading the news. Until the debate became a national and international event for the language competition, such as the ASEAN Qatar debate, which enjoys a prestigious position among the activists of the Arabic language. Debate is also of great importance, as it is one of the effective means of communication, where interlocutors cooperate to know the truth and each party discovers what is hidden, and to follow the path of correct inference to reach the truth, and a window for exchanging and competing ideas as well. As for the objectives of this research: (1) To find out how to teach the scientific debate to improve the speaking. (2) To find out the extent of the effectiveness of teaching scientific debate to improve speaking skill for students. In this research, the researcher used the quantitative approach and its quantitative survey type. As for the data analysis, which is to obtain a Pearson product moment correlative coefficient test, with a ratio of 2-tailed sig value = 0.042 > 0.05, it has a correlation between the X variable and the Y variable, the arithmetic pearson correlation = 0.305, and it has a weak relationship. As for the value from the T test, the value of 0,05 > sig 0, 01, then there is an effect of the X variable on the Y variable. For the value of the t-count greater than the t-table, 408,4 > 1,679, there is a significant effect of the X variable on the variable Y. So the conclusion is that “Ha”is accepted and “Ho” is rejected.